Development of standardized kaffir lime fruit peel extract as a gel for antioxidant and anti-acne - Darsono, Farida Lanawati; Soegianto, Lisa; Jessica, Maria Anabella (Universitas Ahmad Dahlan, 2024)
This study aimed to determine the effect of increasing the concentration of the condensed extract of kaffir lime fruit peel in a gel dosage form on its physical quality and effectiveness. The condensed extract was obtained by maceration with 95% ethanol as a solvent. The dosage form chosen is a hydrophilic-based gel with a modification of the addition of a penetrant enhancer (IPM) and a solubilizer (Glycerin). The concentration of the condensed extract of kaffir lime fruit peel used were F1 (10%), F2 (15%), and F3 (20%). Gel preparations were tested for physical quality and effectiveness, consisting of antioxidant activity (IC50) and antibacterial (Zone Inhibition). Furthermore, the One Way ANOVA statistical method will analyze data from parametric experiments between batches and between formulas. If there is a significant difference in the statistical analysis between the formulas, then the test is continued using the Tukey Post-Hoc test method. The experimental results showed that increasing the concentration of kaffir lime peel extract (Citrus hystrix) affected the pH value, viscosity, dispersion, and effectiveness as an anti- acne and antioxidant. It was concluded that the anti-acne gel of extract F1, F2, and F3 were physically stable during storage, and based on the physical quality and effectiveness test it was known that F3 had the greatest zone inhibition (ZI): 13.87 ± 0.18 mm and IC50 :14.9049 mg/mL